2016
DOI: 10.1108/ecam-03-2015-0040
|View full text |Cite
|
Sign up to set email alerts
|

Construction labor productivity convergence: a conditional frontier approach

Abstract: Purpose -Understanding and simulating construction activities is a vital issue from a macro-perspective, since construction is an important contributor in economic development. Although the construction labor productivity frontier has attracted much research effort, the temporal and regional characteristics have not yet been explored. The purpose of this paper is to investigate the long-run equilibrium and dynamics within construction development under a conditional frontier context. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…LP has been defined in several ways such as the value of gross output per worker (Taymaz, 2002). A simple definition of LP in the literature is the output and an input ratio and has been used as a measurement tool to examine LP (Ma et al, 2016).…”
Section: Domain Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…LP has been defined in several ways such as the value of gross output per worker (Taymaz, 2002). A simple definition of LP in the literature is the output and an input ratio and has been used as a measurement tool to examine LP (Ma et al, 2016).…”
Section: Domain Focusmentioning
confidence: 99%
“…Mark defined productivity as an output of the physical or factual volume of products and services associated with the physical or factual quantities of input (Mark, 1971, p. 7). Several authors have indicated the importance of the LP to ensure the competitiveness of the manufacturing industry in the world market (Ma, Liu, & Mills, 2016; Palel, Ismail, & Awang, 2016). High LP in the manufacturing industry facilitates sustainable growth and economic development of a nation.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…Moreover, the factors were categorized into groups as presented in Table 1. Although many studies discussed labor productivity [5,[18][19][20][21][22][40][41][42], there is a gap in the literature when it comes to ranking labor productivity drivers considering their frequency of occurrence. The previous studies evaluating the labor productivity used only the level of importance without considering the frequency of occurrence of each factor.…”
Section: Motivation For the Studymentioning
confidence: 99%
“…For example the Australian construction industry is the 3rd largest contributor to the GDP of the country (8-9% on an average), and provide employment to 9-10% of the total employment in the country [1], [3], [22]- [24]. Furthermore, it is considered to contribute 12-14% to employment by 2030 [2], [25]. Construction productivity is defined ''as a ratio of a volume measure of output to a volume measure of input use (OECD Manual)" [26,27] [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these parameters were not the only constrained to the success of any construction project. There are much more generalized and sophisticated attributes that impacts productivity of construction projects were: poor site management, continuous over time, site welfare, lack of trust, better training, measurement of productivity, availability of material, frequent design changes, scope clarity, logistics and supply chain management, and many other attributes [1], [3], [23]- [25], [30]- [32].…”
Section: Introductionmentioning
confidence: 99%